Inovasi Guru dalam Mewujudkan Pembelajaran Pendidikan Agama Islam yang Bermakna di Sekolah Menengah Kejuruan Negeri 9 Surakarta - Evi Nurhayati; Dartim Dartim (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines various innovations used by Islamic Religious Education (PAI) instructors at SMK Negeri 9 Surakarta to create meaningful learning. The study employed a qualitative methodology, collecting data through interviews and observations of PAI instructors. The findings demonstrate how instructors employ a participatory, contextual, and student-centered approach to implement various learning innovations. Learning resources are made more understandable and usable by connecting them to students' daily lives and experiences, in addition to providing theoretical support. The development of an engaging and enjoyable learning environment is also facilitated by the use of various learning resources and the introduction of students to religious culture in the classroom. These innovations have a positive impact on increasing student engagement in the learning process, understanding religious material, and strengthening students' religious character. Thus, PAI teachers have a strategic role in creating relevant, engaging, and meaningful learning for students in vocational school environments.